Pengembangan Bioaditif Serai Wangi Pada Bahan Bakar Bensin Terhadap Performa Mesin Dan Emisi Gas Buang Sepeda Motor - Budi Utomo Wisesa; Dahmir Dahlan (Magister Teknik Mesin Universitas Pancasila, 2020)
Bio-additives are elements derived from plants that are utilized as additives to improve fuel quality. Lemongrass fragrant oil is one of the types used as bio-additives that are volatile and soluble into fuels. The purpose of using this bio-additive is to improve the performance of the machine, but the resulting emissions must be in permissible regulations. This research was conducted by experimental methods, some of the tested samples consisted of gasoline (Pertalite), then the development was done by adding the element of lemongrass aromatic bio-additive on the fuel with a ratio of 1.5:1000 ml, 2.0:1000 ml, 2.5:1000 ml, 3.0:1000 ml, and 3.5:1000 ml. The sample test was carried out to measure engine performance, exhaust emissions, using Sportdevice Dyno and Emission Tester. Also, fuel consumption testing is carried out to determine the efficiency of fuel consumption. The results of this study the use of a fragrant lemongrass bio-additive can improve the performance of the motorcycle, maximum power increased by 3.11% at a ratio of 3.0:1000 ml and optimum torque are achieved at 2.03% at a ratio of 2.0:1000 ml. Then the result of exhaust emission measurement of HC and CO elements arising from the use of lemongrass bio-additives is still environmentally friendly In addition to the testing, fuel consumption measurement is also done by generating a savings of 20.93%, mileage 69.9 Km/L ratio using a ratio of 3.5:1000 ml.